Algoritma Floyd Warshall untuk Menentukan Jarak Terpendek dalam Pencarian Oleh-Oleh di Bandar Lampung Berbasis Android - M. Aswan Rahmatullah; Nisar Nisar (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Lampung, a province located at the southern end of Sumatra Island, serves as a gateway for many migrants from different regions in Indonesia. However, some of the locals and tourists still face difficulties in finding the central location for souvenirs due to the vast number of shops available. The purpose of this research is to assist tourists in finding the shortest distance to the nearest souvenir location using the Floyd Warshall algorithm. The software development method employed in this study is the Prototype, which consists of four stages, namely Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, Deployment Delivery & Feedback. In the Rapid Modeling stage, the Floyd Warshall algorithm is used to determine the shortest distance for users to find the souvenir location. The result of this research is an android-based application that can provide the nearest souvenir location with the shortest distance around the user.